The changes in peripheral blood Th17 and Treg ratios in Hashimoto’s thyroiditis are accompanied by differential PD-1/PD-L1 expression - Fang, Jun; Yu, Lei; Zhuang, Lan-Gen; Pei, Xiao-Yan; Wang, Qiong; Jin, Guo-Xi (Frontiers in Endocrinology, 2022)
Objective: This aim of this study was to probe the changes in T helper 17 cells (Th17) and T regulatory (Treg) percentages during autoimmune Hashimoto's thyroiditis (HT), and the expression of the checkpoint molecules programmed death receptor 1/programmed death ligand 1 (PD-1/PD-L1) on these cells. Methods: This study is a case-control study involving 53 initially diagnosed HT patients (HT group) and 21 normal controls (NC group). The peripheral blood mononuclear cells from the individuals of the two groups were isolated and restimulated ex vivo; the percentage of Th17, Treg, PD-1+ Th17, PD-L1+ Th17, PD-1+ Treg, and PD-L1+ Treg cells was assessed by flow cytometric analysis. Results: (1) The percentage of Th17 cells in the peripheral blood of the HT group was significantly higher than that of the NC group ([6.38 ± 1.32]% versus [3.12 ± 0.66]%; t = 14.110, P < 0.001), while the percentage of peripheral blood Treg cells was significantly lower ([3.82 ± 1.48]% versus [5.61 ± 1.60]%; t = −4.599, P < 0.001). (2) HT patients’ Th17 cells expressed PD-1 at a significantly lower frequency than their counterparts in the NC ([6.46 ± 2.77]% versus [18.51 ± 3.96]%; t = −14.842, P < 0.001), while no difference was observed for PD-L1 between the two groups. (3) In contrast, both PD-1 and PD-L1 were expressed at significantly higher frequency on HT patients’ Treg cells than on NC (respectively: [17.01 ± 3.04]% versus [10.23 ± 2.77]%; t = 8.850, P < 0.001 for PD-1; [16.60 ± 9.58]% versus [11.36 ± 10.14]%; t = 2.089, P < 0.005, for PD-L1). Conclusion: (1) The increased percentage of Th17 cells and decreased percentage of PD-1+ Th17 cells in the HT group suggest that a loss of control on Th17 activity through the checkpoint inhibitory axis PD-1/PD-L1 may cause immune injury and participate in disease pathogenesis. (2) The decreased percentage of Tregs in HT patients may explain a lack of regulatory functions able to prevent the autoimmune destruction of the thyroid. Elucidating this apparent contradiction may reveal important mechanisms underlying HT pathogenesis.